Pharmacological management of COVID-19 - Veena Raghunathan; Maninder Singh Dhaliwal (Wolters Kluwer Medknow Publications, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) pandemic has brought the world to a standstill and is the largest public health crisis in the world in the present generation. As the cases continue to increase globally, and more patients are developing severe disease, large volumes of clinical data collection and aggressive research is being carried out to find effective medical therapies for this disease. No definitive proven treatment option exists till date. Various immunomodulatory and anti-viral drugs have shown potential, and are being studied extensively through randomized trials. The most available literature is based on the adult study population, with few/no children being included. This review attempts to summarize the pharmacotherapeutic options presently in consideration in children in the treatment of SARS-CoV2.